Teacher Skills in Leading Small Group Discussions to Class III Students of SD Inpres 10/73 Pandu - Mesra, Romi; Erianjoni, Erianjoni; Tuerah, Paulus Robert; Hamsa, Hamsa; Telaumbanua, Rio Ardika; Lase, Karnius; Gea, Melvin Hariyanti (Technium Social Sciences Journal, 2023)
The purpose of this research is to investigate the abilities of conducting effective small group conversations in the setting of class III students, specifically at SD Inpres 10/73 Pandu. Small group discussions are a collaborative learning technique that can improve student active engagement while also developing critical thinking abilities. This study’s research methodology is a qualitative approach using case study research. Interviews and classroom observations with students and instructors were used to obtain data. The study’s findings indicate that there are various extremely successful strategies of conducting a small group conversation to students/I class III SD Inpres 10/73 Pandu, including providing discussion goals. As discussion guides, we must decide what we want to accomplish in the conversation. Prepare conversation themes and material, prepare discussion topics or material to be discussed, and gather appropriate material or resources. Provide chances for all kids and guarantee that all students may engage in the conversation. Pay close attention to the comments of numerous pupils who wish to present their points or ask questions. The last one employs tactics for leading the appropriate groups and assisting pupils in broadening their thoughts.